Speech by Dr. Eduardo Cáceres Graziani, President of the Peruvian Academy of Surgery and Chairman of the Sixteenth Congress of Surgery Peruvian, in his solemn inaugural session on March 24, 1968 - Cáceres Graziani, Eduardo (2015)
Speech by Dr. Eduardo Cáceres Graziani, President of the Peruvian Academy of Surgery and Chairman of the Sixteenth Congress of Surgery Peruvian, in his solemn inaugural session on March 24, 1968